The Role Of Religious Moderation In Political Dynamics In Indonesia - I Gd. Dedy Diana Putra; I Wayan Budiantara; Ida Ayu Agung Windayani Kusumaharani; Sarono Sarono (Journal of Politica Governo, 2024)
Religious moderation plays a crucial role in shaping the political landscape of Indonesia, a diverse nation characterized by various religious beliefs and practices. This research investigates the significance of religious moderation in navigating the complex political dynamics of the country. Through a comprehensive analysis of primary and secondary sources, including academic literature, governmental reports, and media sources, the study examines how religious moderation influences political behavior, policy-making processes, and interfaith relations in Indonesia. By exploring the impact of religious moderation on electoral outcomes, political discourse, and the overall stability of the political system, this research sheds light on the multifaceted role of moderation in promoting democracy, social cohesion, and inclusive governance. Additionally, the study explores the challenges and opportunities associated with fostering religious moderation in the Indonesian context, offering insights into strategies for enhancing interfaith understanding, tolerance, and cooperation in the pursuit of a more harmonious and equitable society